Intellectual Education in Modern Day Schools - Kulić, Radivoje N.; Minić, Vesna Lj.; Đurić, Igor R. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Pedagogical and psychological sources have long and profoundly dealt with intellectual education and its place and role in the concept of overall personality development. Moreover, it is quite certain that the majority of famous cognitive theories (Piaget, Bruner and Vygotsky) and the emphasized significance and benefit of the humanization of education significantly affect the structure of intellectual education goals in modern day schools. In that context, the structure of intellectual education goals implies the acquisition of knowledge, skills and habits, as well as the enrichment of the intellectual experience of children, and also good psychological basis for the intellectual development of personality.
Keywords: intellectual education; cognitive and intellectual development; intellectual education goals